Malignant hyperthermia crisis during scoliosis surgery in a pediatric cerebral palsy patient: a case of early recognition and successful intervention - Saleh M. Kardm; Abdulmonem Alsiddiky; Asim J. Alamri; Ravi Shankar Reddy (Frontiers in Pediatrics)
BackgroundMalignant hyperthermia (MH) is a rare but life-threatening complication of general anesthesia, characterized by a hypermetabolic response that can lead to severe complications if not managed promptly. Patients with neuromuscular disorders, such as cerebral palsy and neuromuscular scoliosis, may have an increased risk of developing MH due to underlying genetic and physiological factors. Despite its rarity, early recognition and intervention are critical for patient survival.Case presentationWe present a case of MH in a 13-year-old girl with cerebral palsy and neuromuscular scoliosis undergoing elective scoliosis correction surgery under general anesthesia. The patient had no prior history of mental health (MH) susceptibility or a family history of the condition. After 90 min of surgery, she exhibited a rapid increase in end-tidal carbon dioxide (EtCO₂) to 60 mmHg, tachycardia (190 bpm), hypotension (70/40 mmHg), hyperthermia (41°C), and muscle rigidity, raising suspicion of MH. Sevoflurane inhalation was immediately discontinued, and the anesthesia circuit was changed to allow pure oxygen inhalation. The patient was treated with intravenous dantrolene, active cooling measures, forced alkaline diuresis, and correction of acid-base disturbances. These interventions successfully stabilized her vital signs, allowing the surgery to proceed safely. Postoperatively, she was transferred to the intensive care unit (ICU) for monitoring and was extubated once her condition stabilized. She was discharged on postoperative day 7 without further complications.ConclusionThis case highlights the critical need for anesthesiologists and surgical teams to remain vigilant for MH in patients with neuromuscular disorders, even in the absence of a family history. Prompt recognition and immediate intervention with dantrolene and supportive therapies are essential for a favorable outcome. Preoperative MH risk assessment, avoidance of triggering agents, and preparedness for emergency management are crucial in high-risk populations.